Restitution for Child Victims of Sexual Violence Crimes - Simamora, Tesalonika Amazia; Bakhtiar, Handar Subhandi (Al-Risalah, 2026)
This study explores the legal dimensions of restitution for child victims of sexual violence in Indonesia within the framework of legal protection and restorative justice. It aims to analyze the normative legal framework and examine judicial considerations in court decisions related to restitution enforcement. Using a normative juridical approach, the research reviews legal instruments such as Law No. 35 of 2014, Law No. 31 of 2014, and Government Regulation No. 43 of 2017, as well as selected court decisions. Although prior studies have identified challenges in implementing restitution in general, this study highlights a specific gap in analyzing judicial reasoning in sexual violence cases involving children. The findings show that while the legal framework is comprehensive, enforcement remains inconsistent due to limited understanding among law enforcement and weak inter-institutional coordination. Notably, only a few judges applied restitution substantively and progressively, especially in decisions that detailed enforcement mechanisms. This study offers a novel contribution by critically analyzing inconsistencies in judicial application and interpreting how judges integrate the principle of restorative justice. It concludes that practical implementation must be reinforced to ensure restitution fulfills its role as a tool for justice and recovery for child victims.